High alcohol intake in deceased donors has no effect on pancreas graft survival: a registry analysis. (28th December 2016) - Motallebzadeh, Reza; Aly, Mohamed; El‐Khairi, Muna; Drage, Martin; Olsburgh, Jonathan; Callaghan, Christopher J.
Summary: Outcomes of pancreas transplantation from donors with high alcohol consumption are poorly described. The UK Transplant Registry was used to determine whether donor alcohol intake influenced pancreas survival in simultaneous pancreas–kidney (SPK) transplants performed between 2006 and 2012 ( n = 770). Recipients were stratified by donor alcohol intake: group I ( n = 122)—high recent alcohol intake (>21 or >14 units of alcohol/week in males or females, respectively) or previous alcohol abuse and group II ( n = 648)—low/unknown current intake and no previous alcohol abuse. Median current alcohol intake was higher in group I than group II: 36.3 vs. 10 units/week; P < 0.001. One‐ and five‐year pancreas graft survivals were 88.5% and 73.6% in group I, and 87% and 74.9% in group II. There was no difference in unadjusted graft survival between groups I and II ( P = 0.76), and no difference between group II and a subgroup of group I with a donor history of alcohol abuse and high current intake ( P = 0.26), or from donors with current alcohol consumption of >50 units/week ( P = 0.41). Pancreas donors with past alcohol abuse or current high intake are common, and graft outcomes appear to be acceptable. This analysis suggests that high donor alcohol intake, by itself, should not exclude consideration of pancreas transplantation.